2002
DOI: 10.2113/gscanmin.40.4.1069
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Oxygen Isotopic Constraints on the Origin of the Contact-Metamorphosed Bedded Manganese Deposit at Nagasawa, Japan

Abstract: The Nagasawa deposit, in Japan, is a Paleozoic to Mesozoic chert-hosted bedded manganese deposit that has undergone intense contact metamorphism due to intrusion of a granitic pluton ca. 59 to 62 Ma in age. The manganese ores occur as stratiform manganese silicates and quartz-dominant veins. A detailed petrographic and mineralogical study of ore samples reveals that Fe-, Co-, Ni-, Cu-, Zn-, As-, Te-, Pb-, and Bi-minerals (including native elements, sulfides, arsenides, and tellurides) are commonly present in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…The anion total is also higher (< 0.62 apfu) than the theoretical value (3 apfu). A similar anion excess (< 0.44 apfu) in hedleyite was reported by Cepedal et al (2006) but Haruna et al (2002) have reported an anion deficit (0.51 apfu).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The anion total is also higher (< 0.62 apfu) than the theoretical value (3 apfu). A similar anion excess (< 0.44 apfu) in hedleyite was reported by Cepedal et al (2006) but Haruna et al (2002) have reported an anion deficit (0.51 apfu).…”
Section: Discussionsupporting
confidence: 78%
“…The phase compositionally close to hedleyite is characterized by high contents of Sb (0.69 apfu) and Pb (0.16 apfu). The contents of Fe (0.21 apfu) and Cu (0.4) could relate to the surrounding tetrahedrite rather than to any substitution and, likewise, the similar Fe content reported by Haruna et al (2002). Cook et al (2007) proposed that only S, Se, Sb and Pb could enter to the structure of hedleyite and not Cu or Fe.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation